2016
DOI: 10.1371/journal.pone.0160659
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nutritional Metabolism in Transition Dairy Cows: Energy Homeostasis and Health in Response to Post-Ruminal Choline and Methionine

Abstract: This study investigated the effects of rumen-protected methionine (RPM) and rumen-protected choline (RPC) on energy balance, postpartum lactation performance, antioxidant capacity and immune response in transition dairy cows. Forty-eight multiparous transition cows were matched and divided into four groups: control, 15 g/d RPC, 15 g/d RPM or 15 g/d RPC + 15 g/d RPM. Diet samples were collected daily before feeding, and blood samples were collected weekly from the jugular vein before morning feeding from 21 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
100
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 63 publications
10
100
2
4
Order By: Relevance
“…Our current results for DMI and milk production (Table ) were not consistent with previous findings: in other studies, DMI (Schingoethe et al., ; Sun et al., ), milk yield (Batistel et al., ), 4% fat‐corrected milk (Sun et al., ), or yield or percentage of milk protein (Patton, ) changed when RPMet was supplemented. According to AminoCow, using the data from the production trial (DMI, milk yield, milk content of protein and fat), only the adequacies of Lys and Met were less than 110%.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our current results for DMI and milk production (Table ) were not consistent with previous findings: in other studies, DMI (Schingoethe et al., ; Sun et al., ), milk yield (Batistel et al., ), 4% fat‐corrected milk (Sun et al., ), or yield or percentage of milk protein (Patton, ) changed when RPMet was supplemented. According to AminoCow, using the data from the production trial (DMI, milk yield, milk content of protein and fat), only the adequacies of Lys and Met were less than 110%.…”
Section: Discussioncontrasting
confidence: 97%
“…However, Sun et al. () reported that RPMet supplementation at 15 g/day decreased the same parameters. Sun et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that the response to RPM and RPC may be positive in dairy cattle because of their high methylation requirements (Brusemeister & Sudekum, 2006), but their effects on production have not been consistent (Davidson et al, 2008;Sun et al, 2016;Zhou et al, 2016). In this experiment, the lack of response in lamb growth to RPM may have been owing to the low Lys content in the basal diet (Table 1).…”
Section: Resultsmentioning
confidence: 78%
“…Maskaľová et al (2014) suggest the importance of evaluating RPM and choline in ruminants and experiments in various physiological statuses. Previous experiments with dairy cows showed that dietary supplementation with RPM and RPC alleviated negative energy balance, thereby improving feed intake and modulating hepatic lipid metabolism (Sun et al, 2016). Another study showed that the combination of RPM and RPC did not improve milk production, but it did result in a moderate interaction in the energy balance, reducing the megacalories (Mcal) lost per day (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%